Pattern generation for direct-write three-dimensional nanoscale structures via focused electron beam induced deposition - Keller, Lukas; Huth, Michael (Beilstein Journal of Nanotechnology, 2018)
Fabrication of three-dimensional (3D) nanoarchitectures by focused electron beam induced deposition (FEBID) has matured to a level that highly complex and functional deposits are becoming available for nanomagnetics and plasmonics. However, the generation of suitable pattern files that control the electron beam’s movement, and thereby reliably map the desired target 3D structure from a purely geometrical description to a shape-conforming 3D deposit, is nontrivial. To address this issue we developed several writing strategies and associated algorithms implemented in C++. Our pattern file generator handles different proximity effects and corrects for height-dependent precursor coverage. Several examples of successful 3D nanoarchitectures using different precursors are presented that validate the effectiveness of the implementation.
Keywords: focused electron beam induced deposition; nanofabrication; three-dimensional nanostructures